2016
DOI: 10.1080/00343404.2016.1184244
|View full text |Cite
|
Sign up to set email alerts
|

The economic effect of corruption in Italy: a regional panel analysis

Abstract: This paper provides a within-country analysis of the impact of corruption on economic growth using a panel of Italian regions from 1968 to 2011 through a robust measure of corruption. This measure is averaged over 5-year periods to reduce short-run fluctuations and to reduce probable delayed effects, which are typical for latent phenomena such as corruption. The results show a significant negative impact of corruption on long-term growth in all specifications, both on average and for each Italian region. As a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Most of the studies on this topic have been conducted at a cross-country level and have been criticized due to the incomparability of various institutional characteristics (Del Monte & Papagni, 2001;Lisciandra & Millemaci, 2017) and corruption measures across countries (Glaeser & Saks, 2006); thus, a crossregional, within-country study could provide more insight into the consequences of corruption. Indeed, there are some within-country studies that focus on the examples of Italy and the United States (Del Monte & Papagni, 2001;Glaeser & Saks, 2006;Lisciandra & Millemaci, 2017). However, regional studies of developed countries could not be generalized to other countries around the world, where most are considered developing, with rampant corrupt activities (Glaeser & Saks, 2006).…”
Section: 1 Average Corruption Index 95% CImentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studies on this topic have been conducted at a cross-country level and have been criticized due to the incomparability of various institutional characteristics (Del Monte & Papagni, 2001;Lisciandra & Millemaci, 2017) and corruption measures across countries (Glaeser & Saks, 2006); thus, a crossregional, within-country study could provide more insight into the consequences of corruption. Indeed, there are some within-country studies that focus on the examples of Italy and the United States (Del Monte & Papagni, 2001;Glaeser & Saks, 2006;Lisciandra & Millemaci, 2017). However, regional studies of developed countries could not be generalized to other countries around the world, where most are considered developing, with rampant corrupt activities (Glaeser & Saks, 2006).…”
Section: 1 Average Corruption Index 95% CImentioning
confidence: 99%
“…A huge disparity exists between nations, not only in their levels of corruption but also in other institutional elements, such as administrative control, government subsidies, or the number of state-owned enterprises, which cross-country data are incapable of controlling for. Studies on regions within a country with more homogeneous characteristics could moderate any omitted variable bias that emerged from those differences (Del Monte & Papagni, 2001;Lisciandra & Millemaci, 2017). In addition, cross-country studies often depend on survey-based corruption data, which raises two concerns that have been discussed by Glaeser and Saks (2006).…”
Section: Corruption Effects On Regional Economic Performancementioning
confidence: 99%
See 2 more Smart Citations
“…It is held by a multitude of economists that corruption is an important obstacle of economic growth [3]- [6], and many scholars conducted wide-spread research on the impacts of corruption in economic growth using the cross-country samples, and they unanimously found that [7]- [10] corruption features significant negative impacts on economic growth and investment growth.…”
Section: Literature Reviewmentioning
confidence: 99%